Peritoneal carcinomatosis with desmoplasia and osseous metaplasia mimicking encapsulating peritoneal sclerosis in a cat: case report - Nam, So-Jeong; Song, Sun-Hye; Lee, Seung-Hyun; Jeung, So-Young; Ah, Jae Gon; Lee, Su-Hyung; Ryu, Min-Ok (Frontiers in Veterinary Science, 2023)
A 13-year-old neutered male Korean short-hair cat presented with anorexia, lethargy, and a severely distended abdomen, suggestive of ascites. Abdominocentesis yielded serosanguineous fluid. A subsequent diagnostic workup, including blood tests, ascitic fluid analysis, imaging studies (radiography, ultrasound, computed tomography (CT)), and histopathological examination, was performed to identify the underlying cause. Imaging studies revealed characteristics of encapsulating peritoneal sclerosis (EPS) such as peritoneal thickening, fat stranding, and calcification. During laparotomy, fibrous membranes encapsulating the abdominal organs and ascites were observed, and multiple calcified regions were detected on the abdominal wall. Histopathological analysis confirmed the diagnosis of poorly differentiated invasive malignant neoplasms, which were further classified as carcinomatosis based on positive cytokeratin and negative vimentin immunohistochemistry results. To our knowledge, this is the first report of sclerosing peritoneal carcinomatosis with osseous metaplasia in a cat.